Effect of High Energy Milling Time of the Aluminum Bronze Alloy Obtained by Powder Metallurgy with Niobium Carbide Addition - Dias,Alexandre Nogueira Ottoboni (2017)
The aluminum bronze alloy is part of a class of highly reliable materials due to high mechanical strength and corrosion resistence being used in the aerospace and shipbuilding industry. It's machined to produce parts and after its use cycle, it's discarded, but third process is considered expensive and besides not being correct for environment reasons. Thus, reusing this material through the powder metallurgy (PM) route is considered advantageous. The aluminum bronze chips were submitted to high energy ball milling process with 3% of niobium carbide (NbC) addition. The NbC is a metal-ceramic composite with a ductile-brittle behaviour. It was analyzed the morphology of powders by scanning electron microscopy as well as particle size it was determined. X ray diffraction identified the phases and the influence of milling time in the diffractogram patterns. Results indicates that milling time and NbC addition improves the milling efficiency significantly and being possible to obtain nanoparticles.